Predictive Risk Assessment of D-Dimers and Troponin Levels of Thrombotic Events among COVID-19 Patients in a Community-Based Hospital, New York City - Ruchi Yadav; Beka Aroshidze; Vivek Yadav; Umar Zahid; Apoorva Jayarangaiah; Anjula Gandhi; Vladimir Gotlieb (Medicine and Medical Research: New Perspectives Vol. 5, 2024)
The coronavirus disease 2019 (COVID-19) continues to pose an unprecedented challenge for the entire world and the healthcare system. The role of D-dimer and troponin-I as markers of thrombosis or procoagulant state in COVID-19 infection has been under investigation since the inception of this disease. Different theories have been proposed elucidating the pathophysiological mechanisms attributing to high mortality and morbidity in COVID-19 infection. Out of them, thrombosis and procoagulant state have managed to earn the maximum limelight. The main objective of our study was to assess the risk and occurrence of thrombotic events (both venous and arterial) among hospitalized patients including the intensive care unit (ICU) and non-ICU admissions with confirmed COVID-19 infection. An observational study was conducted based on data from randomly selected 349 hospitalized patients with COVID-19 infection in a community-based hospital in New York City during the first wave of the COVID-19 viral surge in March 2020. Diagnoses were made during the inpatient clinical care, as screening for thrombotic events is not a standard method. The statistical analysis involved non-normally distributed continuous variables that were described as the median and interquartile range (IQR) while mean and standard deviation were used to describe normally distributed continuous variables. The primary outcome in our study was defined as the thrombotic events that included myocardial infarction (MI), deep venous thrombosis (DVT), cerebrovascular accidents (CVA), and pulmonary embolism (PE). The study correlated the association of thrombotic events with the level of biomarkers of interest: D-dimer >1000 ng/ml, troponin-I >1 ng/ml, or both. The association of D-dimers and troponin-I with thrombotic events was measured using both univariate and multivariate Cox proportional hazard (PH) regression analysis. Out of a total of 349 patients, 78 patients (22.35%) were found to have elevated biomarkers (D-dimer >1000 ng/ml and/or troponin-I >1 ng/ml) and were categorized as a high-risk group. Eighty-nine patients developed thrombotic complications (evidence of more than one thrombotic event was found in several patients). Two-hundred seventy-one (77.65%) patients had no documentation of thrombosis. The in-patient mortality rate among patients in our study group, with a high risk of thrombotic events was 44.87% (35/78) as compared to 38.80% (104/271) in patients without any thrombotic events. The incidence of thrombotic events included myocardial infarction (MI; N=45; 12.8%), cerebrovascular accidents (CVA; N=16; 4.5%), deep venous thrombosis (DVT; N=16; 4.5%), and pulmonary embolism (PE; N=9; 2.57%). The lack of prior immunity to COVID-19 has resulted in large numbers of infected patients across the globe and uncertainty regarding the management of the complications that arise in the course of this viral illness. Although D-dimer, sepsis, and microvascular thrombosis are associated with mortality, current data are inconclusive for the use of therapeutic doses of anticoagulation for these findings. With the resurgence of the COVID-19 wave, it is imperative to focus on optimal diagnostic and prophylactic strategies to prevent thromboembolic events and potentially improve survival in COVID-19 patients.